2021
DOI: 10.1108/bjm-06-2021-0219
|View full text |Cite
|
Sign up to set email alerts
|

Inclusive leadership and employee work engagement: a moderated mediation model

Abstract: PurposeThe purpose of this paper is to examine the relationship between inclusive leadership and employee work engagement by identifying person-job fit as a mediator, and employee felt responsibility as a moderator.Design/methodology/approachEmploying a two-wave survey from 261 employees across various industries in China, the study tests hypotheses using hierarchical regression analysis with the PROCESS procedure developed by Hayes.FindingsThe results show that inclusive leadership is positively related to em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 41 publications
0
10
0
1
Order By: Relevance
“…First, based on the fundamental tenet of the COR theory regarding the role of resources in helping individuals cope effectively with threatening situations (Gong et al. , 2023), our results demonstrate that trait mindfulness and functional flexibility could be the personal resources that facilitate the ability for salespeople to deal effectively with challenging market conditions, thereby enabling them to achieve high sales performance.…”
Section: Discussionmentioning
confidence: 82%
“…First, based on the fundamental tenet of the COR theory regarding the role of resources in helping individuals cope effectively with threatening situations (Gong et al. , 2023), our results demonstrate that trait mindfulness and functional flexibility could be the personal resources that facilitate the ability for salespeople to deal effectively with challenging market conditions, thereby enabling them to achieve high sales performance.…”
Section: Discussionmentioning
confidence: 82%
“…First, this study indicates that leaders have the power to increase employees' resilience capacity and task performance by exhibiting enhanced inclusive leadership behavior. Combined with the benefits of inclusive leadership stated by other researchers (Bao et al. , 2021; Katsaros, 2022; Roberson and Perry, 2022), whether in healthcare or other types of organizations, we recommend that managers be committed to cultivating an inclusive leadership style, especially during times of crisis.…”
Section: Discussionmentioning
confidence: 86%
“…Accordingly, employees are more motivated to fulfill their roles and make more cognitive, emotional, and physical contributions to the organization (Choi et al, 2015). Previous studies have revealed that inclusive leadership has a positive relationship with employees’ work engagement (Aslan et al, 2021; Bao et al, 2021; Choi et al, 2015; Wang et al, 2019). Some studies have also found that inclusive leadership indirectly affects work engagement through psychological safety (Aslan et al, 2021; Nembhard & Edmondson, 2006) and employee creativity (Carmeli et al, 2010; Suk et al, 2015).…”
Section: Inclusive Leadershipmentioning
confidence: 99%